2013
DOI: 10.1111/lam.12195
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of isoimperatorin, alone and in combination, against Mycobacterium tuberculosis

Abstract: This is the first report on the in vitro synergistic antimycobacterial effects of isoimperatorin (IO) in combination with three first-line drugs: rifampin (RMP), isoniazid (INH) and ethambutol (EMB). The results indicated that the antimycobacterial activity of IO was modest; however, IO was a useful and effective agent against Myco. tuberculosis when it was combined with first-line antimycobacterial drugs and is worthy of further development as a lead compound for the development of novel antimycobacterial the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…It was reported that coumarins possessed various pharmacological effects, such as imperatorin, which had the antihypertensive, antioxidant [5], anti-inflammatory [6], anti-cancer [7], anticonvulsant [8], vasodilatation [9], and anti-HIV-1 [10] activities, and the prevention on lipopolysaccharide (LPS)-induced acute lung injury [11], cerebral ischemia [12], cardiac hypertrophy and heart failure [13]. Isoimperatorin was found to have the anti-Mycobacterium tuberculosis [14] and anti-inflammatory [15] activities, as well as prevention on aflatoxin B 1 -inducible cytotoxicity [16]. Phellopterin was a partial agonist of the central benzodiazepine receptors in vitro [17] with the anti-inflammatory activity [18].…”
Section: Var Formosana (Boiss) Shan Et Yuan CV Chuanbaizhi (Radfc)mentioning
confidence: 99%
“…It was reported that coumarins possessed various pharmacological effects, such as imperatorin, which had the antihypertensive, antioxidant [5], anti-inflammatory [6], anti-cancer [7], anticonvulsant [8], vasodilatation [9], and anti-HIV-1 [10] activities, and the prevention on lipopolysaccharide (LPS)-induced acute lung injury [11], cerebral ischemia [12], cardiac hypertrophy and heart failure [13]. Isoimperatorin was found to have the anti-Mycobacterium tuberculosis [14] and anti-inflammatory [15] activities, as well as prevention on aflatoxin B 1 -inducible cytotoxicity [16]. Phellopterin was a partial agonist of the central benzodiazepine receptors in vitro [17] with the anti-inflammatory activity [18].…”
Section: Var Formosana (Boiss) Shan Et Yuan CV Chuanbaizhi (Radfc)mentioning
confidence: 99%
“…This compound is present in Angelica dahurica, Notopterygium incisum, Ferula lutea, Angelica pubescens, and Peucedanum praeruptorum. Isoimperatorin exhibits various pharmacological activities, including antioxidant [255,256], anti-inflammatory [257], analgesic [258], antibacterial [259,260], and anticancer properties [261,262]. Wijerathne et al reported that isoimperatorin protected against OA-induced asthma via mitigation of airway inflammation and mucus hypersecretion evidenced by the decreased IL-4, IL-5, and IL-13 production [257].…”
Section: Fraxin Fraxin (7-hydroxy-6-methoxy-8-[(2s3r4s5s 6rmentioning
confidence: 99%
“…Qianghuo (Notopterygium) is widely used in anti-inflammatory, anti-oxidation, anti-arrhythmia, antibacterial, anti-cancer cell proliferation and other treatments [34] [35]. Isoimperatorin (IO), a furanocoumarin isolated from Qianghuo (Notopterygium), shows prominent activity against mycobacterium tuberculosis and nematodes [36] [37]. Furthermore, IO effectively inhibits ovalbumin-induced inflammatory cell infiltration and mucus production to relieve symptoms of asthma [38].…”
Section: The Pharmacological Basis Of "Hanshi Zufei Decoction"mentioning
confidence: 99%